2005
DOI: 10.1213/01.ane.0000167283.80463.d7
|View full text |Cite
|
Sign up to set email alerts
|

The Suppressive Effects of Oxcarbazepine on Mechanical and Cold Allodynia in a Rat Model of Neuropathic Pain

Abstract: Oxcarbazepine (OCBZ) is a keto analog of carbamazepine (CBZ) and may have similar analgesic properties to CBZ, but studies on its effects in neuropathic pain conditions are rare. In this study, we evaluated the analgesic effects of OCBZ in a rat neuropathic pain model. Male Sprague-Dawley rats were prepared by tightly ligating the left L5 and L6 spinal nerves to produce neuropathic pain. Sixty neuropathic rats were randomly assigned into six groups, and normal saline, a vehicle (polyethylene glycol 400), and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Therefore, developing novel therapeutic strategies is necessary. Peripheral nerve injury such as CCI leads to mechanical and thermal hyperalgesia [4245] and also provokes a reaction in peripheral immune and spinal cord glial cells [46]. The current study showed that AS reduced CCI-induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, developing novel therapeutic strategies is necessary. Peripheral nerve injury such as CCI leads to mechanical and thermal hyperalgesia [4245] and also provokes a reaction in peripheral immune and spinal cord glial cells [46]. The current study showed that AS reduced CCI-induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 50%
“…After surgery, the rats were allowed to recover for 7 days before starting the behavioral tests. Those animals that showed a foot withdrawal response to the von Frey filaments (Semmes Weinstein Von Frey Aesthesiometers, Stoelting CO, IL, USA) with an applied bending force of 4 g or less were considered to be neuropathic [20–22], and they were used in the tests. The rats that exhibited motor deficiency (such as paw dragging or limping) or those that failed to exhibit subsequent mechanical allodynia were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The animals we used in the tests were those that showed a foot withdrawal response to von Frey filaments (Semmes Weinstein von Frey esthesiometer, Stoelting Co., IL, USA), with an applied bending force of B 4 g considered neuropathic. 19 The rats that exhibited motor deficiency, such as paw dragging or limping, or those that failed to exhibit subsequent mechanical allodynia were excluded from any further testing.…”
Section: Spinal Nerve Ligationmentioning
confidence: 99%